The factors influencing Maldivian teachers' professional agency during curriculum reform - Mohamed, Lawsha (Kulliyyah of Education, International Islamic University Malaysia, 2021)
This study examined the influence of four factors, namely personal capacity, beliefs, aspirations, and school climate in the exercise of teachers' professional agency during curriculum reform in the Maldives. To achieve this aim, the study developed and evaluated the adequacy of measurement models of personal capacity, beliefs, aspirations, and school climate to examine their relationship with teachers' professional agency. Survey data were collected from 360 teachers from 13 government primary schools located in Male' city, the capital of Maldives. The questionnaire measured professional agency and its underlying factors with 38 items rated on a 7-point Likert-type scale. An exploratory factor analysis followed by a confirmatory factor analysis revealed that the measurement models and the full-fledged structural model of professional agency fit the data collected from the Maldivian teachers. Furthermore, the analysis provided evidence for the convergent and discriminant validity and composite reliability of the scales indicating the adequacy of all measurement models. The results of Structural Equation Modelling analysis revealed that personal capacity and beliefs significantly and positively influenced teachers' professional agency as the study had hypothesized. However, the other two proposed constructs, school climate and aspirations, were not significant correlates of agency. More significantly, the study has theoretically and empirically validated a structural model of factors influencing teachers' professional agency during curriculum reform with important practical implications. The findings should guide relevant authorities in the Maldivian teacher education system to plan and implement results-driven training for both in-service and pre-service teachers to develop and further enhance their capacities towards professional agency.